An Activity Scale for All Youth Athletes? Clinical Considerations for the HSS Pedi-FABS. Issue 12 (22nd December 2022) - Carpenter, Connor M.; Cooper, Savannah B.; Wilson, Philip L.; Miller, Shane M.; Wyatt, Charles W.; Johnson, Benjamin L.; Shea, Kevin G.; Ellis, Henry B.
Background: The Hospital for Special Surgery Pediatric Functional Activity Brief Scale (HSS Pedi-FABS) has demonstrated normally distributed scores in children aged 10 to 18 years. It has been used to evaluate knee injuries; however, there is limited information regarding its use in evaluating other injury types. Purpose: To (1) assess the validity and utility of HSS Pedi-FABS in youth athletes with injuries to different parts of the body and (2) evaluate the association between the HSS Pedi-FABS and the Patient-Reported Outcomes Measurement Information System (PROMIS) Pediatric Global Health 7 (PGH), as well as PROMIS–Pain Interference (PGH-PI) and PROMIS-Fatigue (PGH-F) components. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: The authors performed a retrospective review of youth athletes aged 10 to 18 years who completed the HSS Pedi-FABS as part of their previsit intake questionnaire between April 2016 and July 2020. HSS Pedi-FABS score distributions were compared and evaluated for ceiling effects in cohorts determined by demographic, injury characteristic, and sports participation variables; a ceiling effect was determined to be present if >15% of respondents received the highest possible score. HSS Pedi-FABS scores were analyzed for a correlation with PGH, PGH-PI, and PGH-F components. Results: Included were 2274 patients (mean age, 14.6 ± 2.1 years; 53.0% female) participating in 21 distinct primary sports for 9.6 ± 7.9 hours per week. The mean HSS Pedi-FABS scores by injury group were as follows: elbow (22.7 ± 6.7), shoulder (21.0 ± 8.7), ankle (20.2 ± 8.8), knee (19.5 ± 9.1), and hip (15.4 ± 10.4) ( P < .001). Broad distribution was seen in each cohort, with no floor or ceiling effects. The HSS Pedi-FABS score correlated with patient-reported hours per week ( r = 0.33), days per week ( r = 0.33), and years of participation ( r = 0.21) ( P < .001 for all). All 3 PROMIS components correlated with HSS Pedi-FABS: PGH ( r = 0.28), PGH-PI ( r = –0.11), and PGH-F ( r = –0.15) ( P < .001). Conclusion: Study findings indicated that the HSS Pedi-FABS is a valid tool for measuring physical activity level in most injured youth athletes, not just those with knee injuries. The correlation of HSS Pedi-FABS with the PGH suggests a positive relationship of childhood physical activity with general health.